2020
DOI: 10.1371/journal.pbio.3000958
|View full text |Cite
|
Sign up to set email alerts
|

Differences in structure and hibernation mechanism highlight diversification of the microsporidian ribosome

Abstract: Assembling and powering ribosomes are energy-intensive processes requiring fine-tuned cellular control mechanisms. In organisms operating under strict nutrient limitations, such as pathogenic microsporidia, conservation of energy via ribosomal hibernation and recycling is critical. The mechanisms by which hibernation is achieved in microsporidia, however, remain poorly understood. Here, we present the cryo–electron microscopy structure of the ribosome from Paranosema locustae spores, bound by the conserved euk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 50 publications
4
51
0
Order By: Relevance
“…Compared to the previously determined structures of V. necatrix and P. locustae ribosomes (both structures represent the same family of Nosematidae microsporidians and are very similar to each other) 31 , 32 , E. cuniculi ribosomes underwent further degeneration of numerous rRNA and proteins segments (Supplementary Figs. 4 – 6 ).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Compared to the previously determined structures of V. necatrix and P. locustae ribosomes (both structures represent the same family of Nosematidae microsporidians and are very similar to each other) 31 , 32 , E. cuniculi ribosomes underwent further degeneration of numerous rRNA and proteins segments (Supplementary Figs. 4 – 6 ).…”
Section: Resultsmentioning
confidence: 84%
“…E. cuniculi is a fungi-like organism, which belongs to the group of parasites microsporidia, which possess anomalously small eukaryotic genomes and are therefore used as model organisms to study genome decay 25 – 30 . Recently, cryo-EM structures of ribosomes were determined for microsporidians with moderately reduced genomes, Paranosema locustae and Vairimorpha necatrix 31 , 32 (~3.2 Mb genomes). These structures showed that the loss of some rRNA expansions is compensated by evolving new contacts between adjacent ribosomal proteins or by the acquisition of a new ribosomal protein, msL1 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A loss of function of Dis3L proteins is linked to many human diseases ( 62 , 81 ). Hibernating 80S ribosomes are relatively stable ( 6 , 7 , 19 ), and it remains to be determined whether they are protected by preclusion of the action of Dis3L exonucleases and known ribosome degradation pathways such as the ubiquitin-proteasome system and ribophagy ( 82 ). Our discovery fills the knowledge gap between ribosome hibernation and turnover and may delineate general principles of RNase R function in all kingdoms of life.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian equivalent of 100S, a dimer of 80S monomers (110 complex), has only been observed in tumor cells under nutrient starvation ( 18 ). Adding to the dissimilarity, eukaryotic hibernation factors (Lso2/CCDC124 and Stm1/SERBP1) clamp the 40S and 60S subunits together to form an inactive 80S complex ( 6 , 7 , 19 ).…”
Section: Introductionmentioning
confidence: 99%